Kepraktisan dan Tingkat KeterbacaanBahan Ajar Matakuliah Sintaksis Bahasa Indonesia Berbasis Peta Konsep - Astuti, Tri; Muslihah, Nur Nisai; Herliyansyah, Raynaldi Bintang; Arora, Novus Adelia; Purwati, Eka (JURNAL PERSPEKTIF PENDIDIKAN, 2025)
This study aims to describe the development, practicality, and readability of a concept map–based Indonesian Syntax textbook designed to support learning in higher education. The textbook consists of ten chapters aligned with the formulated learning outcomes and is presented systematically from fundamental syntax concepts to advanced analytical materials. The content is complemented with various visual representations, including tree diagrams, box schemes, and functional analysis models, as well as enrichment exercises at the end of each chapter to strengthen students’ comprehension. The practicality of the textbook was assessed through three stages of student response testing: one-to-one trials involving 3 students, small-group trials involving 9 students, and field trials with 27 students, using a closed–ended response questionnaire consisting of 20 items. The results show an overall practicality rate of 91.28%, categorized as very practical. Readability assessment was conducted through a 60–item objective post-test administered to 27 students, resulting in an average score of 81.67, classified as very good. These findings indicate that the textbook is feasible, practical, and highly readable to be implemented as a learning resource in Indonesian syntax courses.